The Prevalence of Headache in Crohn’s Disease: Single-Center Experience - Ulker Anadol Kelleci; Turan Calhan; Abdurrahman Sahin; Resul Kahraman; Kamil Ozdil; Haci Mehmet Sokmen; Destina Yalcin (Gastroenterology Research and Practice)
Objectives. This study is aimed at studying the prevalence and characteristics of different types of headaches in patients with Crohn’s disease. Materials and Methods. 51 patients in Crohn’s disease group (F/M: 26/25) and 51 patients in control group (F/M: 27/24) were involved. Patients in Crohn’s disease group were diagnosed and monitored according to European Crohn’s and Colitis Organization diagnostic criteria. The control group composed of healthy subjects with similar age and sex to Crohn’s disease group. Headache was classified using the International Headache Society II criteria. Results. Headache was reported by 35/51 (68.6%) patients in Crohn’s disease group and 21/51 (41.2%) patients in the control group. The prevalence of headache was statistically high in the group with Crohn’s disease (OR: 3.125 (95% CI: 1.38–7.04); p=0.01). Comparing two groups with respect to their subtypes of headaches resulted in that the tension-type headache was statistically (p=0.008) higher in Crohn’s disease group (26/51) than in the control group (12/51). However, no significant difference was found in the migraine-type headache (p=1). Conclusions. This study indicates that the prevalence of headache is high in patients with Crohn’s disease and most commonly associated with the tension-type headache.